Dimensional And Mechanical Deviation Of Paving Block Type Rectangular From Several Manufacturers In Semarang City - Mudiyono, Rachmat; Wibowo, Titus Tony (Universitas Islam Sultan Agung, 2024)
The non-uniformity of paving block quality can result in uneven pavement, which in turn can increase the risk of traffic accidents. This study aims to determine the quality of compressive strength of paving block type Holland from several manufacturers in Semarang City area both manually and massively. As well as knowing why the physical dimensions of paving block type Holland from several producers in Semarang City are not uniform. This research was conducted by taking samples in the paving block manufacturing industry around the city of Semarang. The discussion in this study only covers the type of holland paving block in Semarang City from 4 producers namely CV Waringin Putih Banyumanik Semarang, PT Alam Daya Sakti, Anugerah Block, and Putra Alam Sari. All paving block products tested met or exceeded the minimum value of compressive strength specified in SNI 03- 0691-1998. This indicates that these products have an adequate ability to withstand the given compressive load. The compressive strength test results show that the lowest value was recorded for Anugrah Block at 17.21 MPa, while the highest value was achieved by PT Alam Daya Sakti with 20.112 MPa. The non-uniformity of the physical dimensions of Holland type paving from several producers in Semarang City can be influenced by several factors, including different production processes between producers, the use of different raw materials, and differences in the arrangement of machines or production equipment.